2014
DOI: 10.1128/aac.02462-13
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Ceftolozane-Tazobactam Resistance Development Requires Multiple Mutations Leading to Overexpression and Structural Modification of AmpC

Abstract: bWe compared the dynamics and mechanisms of resistance development to ceftazidime, meropenem, ciprofloxacin, and ceftolozane-tazobactam in wild-type (PAO1) and mutator (PAOMS, ⌬mutS) P. aeruginosa. The strains were incubated for 24 h with 0.5 to 64؋ MICs of each antibiotic in triplicate experiments. The tubes from the highest antibiotic concentration showing growth were reinoculated in fresh medium containing concentrations up to 64؋ MIC for 7 consecutive days. The susceptibility profiles and resistance mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
160
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(174 citation statements)
references
References 36 publications
8
160
1
5
Order By: Relevance
“…Interestingly, ceftolozane-tazobactam MIC values for these mutant strains were still low (17). Six isolates displaying OprD loss and derepression of MexABOprM had modestly elevated median MIC values for cephalosporins and ␤-lactam/␤-lactamase inhibitor combinations (from 0.5 to 16 g/ml) and elevated median MIC values for imipenem and meropenem (8 g/ml for both carbapenems) ( Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, ceftolozane-tazobactam MIC values for these mutant strains were still low (17). Six isolates displaying OprD loss and derepression of MexABOprM had modestly elevated median MIC values for cephalosporins and ␤-lactam/␤-lactamase inhibitor combinations (from 0.5 to 16 g/ml) and elevated median MIC values for imipenem and meropenem (8 g/ml for both carbapenems) ( Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…However, when analyzing isolates carrying AmpC derepression with hyperexpression of one or more tripartite efflux systems, the median MIC values were elevated for ceftazidime, cefepime, and piperacillin-tazobactam (median MIC ranges, 32 to Ͼ32, 16 to Ͼ16, and 64 to Ͼ64 g/ml, respectively) but not for carbapenems (Table 4). In a recent study, Cabot et al (17) evaluated meropenem-induced mutants and observed that these strains displayed OprD deficien- (8) OprD loss, MexAB-OprM overexpression…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its activity is adversely affected by increased efflux in A. baumannii and P. aeruginosa (955). Moreover, several new cephalosporin-␤-lactamase-inhibitor combinational products in clinical trials (e.g., ceftazidime-avibactam, ceftaroline-avibactam, and ceftolozane-tazobactam) (944) are still likely to be the substrates of RND pumps, as are other ␤-lactams and ␤-lactamase inhibitors (13,390,439,545), because avibactam cannot reverse efflux-mediated ceftazidime resistance (956), and both ceftaroline and ceftolozane (a new antipseudomonal cephalosporin) are still affected by efflux pump-and/or porin-related resistance mechanisms (although ceftolozane, containing multiple charged groups, appears less impacted by Mex pumps than many other ␤-lactams and did not select in vitro for pump overproducers in P. aeruginosa, unlike other agents) (417,(957)(958)(959). These observations could also illustrate their reduced or lack of synergistic activity against multidrug-resistant A. baumannii and P. aeruginosa (960)(961)(962).…”
Section: Multidrug Efflux Pumps As a Challenge In Drug Developmentmentioning
confidence: 99%
“…69 The development of resistance to ceftolozane tazobactam among strains of P. aeruginosa has been reported to be slower than resistance to other antipseudomonal agents, and it remained active against mutants resistant to ceftazidime, ciprofloxacin, and meropenem. 70 Spectrum of activity of ceftolozane/ tazobactam includes difficult-to-treat Gram-negative pathogens, including ESBL strains. 28,[71][72][73] Another new therapeutic option is represented by ceftazidime/avibactam, where the new b-lactam inhibitor agent avibactam improves the activity of ceftazidime against MDR P. aeruginosa.…”
Section: New Antibioticsmentioning
confidence: 99%